National Brand of Armenia in the Context of Public Diplomacy - Airapetova, Ruzanna (YSU Journal of International Affairs, 2022)
The purpose of the article is to determine the development trend of the national brand of Armenia. In its turn, the research is tasked with studying the influence and place of national branding in the public diplomacy of the state, the possibilities of national branding to resist negative stereotypes and form positive associations aboutthe country. In the course of the study, it was defined that the results of national brandingcontribute to a positive impact on the development of public diplomacy, which in its turn affects the expansion of branding opportunities. In its turn, the absence of the implementation of the national brand leads to restrictions in the implementation of foreign policy. The article makes an attempt to define an effective brand for Armenia in the context of brand identity. Through the method of case studies, the article presents ananalysis of each particular stage of development. Solving the issues of positioning the country, the study presents the concepts of “brand”, “image” and “reputation”. The interrelation of these concepts lies in the fact that image and reputation are the derivative result of the activities of national branding. The research presents theoretical approaches of international experts to the formation of a national brand. Based on theapproaches studied, there are reputational factors that influence the formation of an image: emotional, resource and power.
Keywords: national branding; public diplomacy; image; reputation; brand; stereotype; competition; competitive struggle